The role of practical activities in teaching mechanical systems and control - Msimango, Esie Zandile; Mtshali , Thokozani Isaac (Indonesian Institute for Counseling, Education and Therapy (IICET), 2025)
This study examined the role of practical activities in teaching Mechanical Systems and Control in Grade 8 Technology classrooms. Pedagogical practices play a vital role in facilitating learners’ understanding of abstract mechanical concepts such as levers, pulleys and gears, particularly within under-resourced schools in South Africa. The study adopted a qualitative exploratory case study design and was conducted in the Madibeng Sub-District of the North West Province. Seven Grade 8 Technology educators were selected using expert purposive sampling. Data were collected through semi-structured interviews and open-ended questionnaires to explore educators’ pedagogical practices, use of practical activities and perceived learner outcomes. The data were analysed using thematic analysis, following a systematic coding and categorisation process to identify key patterns and themes. The findings indicate that practical activities enhance learner participation, improve conceptual understanding and support the development of problem-solving skills by making abstract mechanical concepts more tangible and relatable. However, the findings also reveal challenges related to limited resources, time constraints and variations in educators’ pedagogical content knowledge, which affect the effective implementation of practical work. Trustworthiness was ensured through data triangulation and participant checking. The study is limited by its small sample size and focus on a single sub-district, which restricts generalisability. Despite these limitations, the study highlights important implications for teacher support, resource provision and pedagogical improvement in Technology education.